Simulation of pollutant transport in mobile water-flow channels in permafrost environment - E. I. Debolskaya; A. V. Ostyakova (Лëд и снег, 2015)
A common problem for the Arctic region is pollution by persistent organic compounds and other substances that have accumulated over the years in these areas. With temperature increasing, these substances can get out of the snow, ice, permafrost in the human environment. With climate warming and permafrost degradation the risk of toxic substances from the burial sites of chemical and radioactive waste increases. The work is devoted to research the pollution propagation in the rivers flowing in the permafrost taking into account the possible deformations of the channels caused by the melting of the permafrost with increasing temperature of the river flow water. We also consider the distribution of pollutants released during erosion of the coastal slopes, caused thermal erosion. Numerical experiments confirmed the quantitative assessment obtained from the field observations of the erosion rate increases with increasing temperature. Study the impact of thermal and mechanical erosion of the distribution of impurities led to the conclusion that as a result of the formation of taliks uniform flow conditions are violated, resulting in a non-stationary distribution of impurities. The increase in the volume of the test section of the river due to the appearance of cavities in the coastal slope leads to an increase in impurity concentration. Analysis of the results of modeling the spread of contamination during thawing sources in the frozen shores, demonstrated the relationship in the process of distribution of impurities from the position of the source and allowed to give a preliminary quantitative assessment.